Peran Guru Dan Sekolah Dalam Mewujudkan Pendidikan Anti Narkoba Di Sekolah Dasar Gugus II Jebres Surakarta - Roviqoh Budiono; Wahdan Najib Habiby (Elementary Teacher Education Program, Majalengka University, 2023)
This study aims to 1) find out how elementary schools are realizing anti-drug education. 2) knowing the role of teachers in anti-drug education. Data collection techniques used in this study were interviews and observation. Validation of the data using other research triangulation, re-checking and verification of respondents. Data analysis techniques with data reduction, data presentation and drawing conclusions. The results showed that 1) The school's role in realizing anti-drug education in elementary schools was carried out by the principal. There are many things that can be done by a school principal to realize anti-drug education in his school. One way the principal makes policy. Policies made can be a guide in attitude for students, teachers, and all school members while in the school environment. 2) The role of teachers in anti-drug education in elementary schools is to provide knowledge. Teachers play an active role in providing all kinds of knowledge about drugs to students. This knowledge is given with the aim that elementary school students are aware of the dangers of drugs and form confidence in themselves not to try to recognize or even consume drugs.